Cdk Activity Couples Epigenetic Centromere Inheritance to Cell Cycle Progression - Silva, Mariana C.C. (2016)
Centromeres form the site of chromosome attachment to microtubules during mitosis. Identity of these loci is maintained epigenetically by nucleosomes containing the histone H3 variant CENP-A. Propagation of CENP-A chromatin is uncoupled from DNA replication initiating only during mitotic exit. We now demonstrate that inhibition of Cdk1 and Cdk2 activities is sufficient to trigger CENP-A assembly throughout the cell cycle in a manner dependent on the canonical CENP-A assembly machinery. We further show that the key CENP-A assembly factor Mis18BP1(HsKNL2) is phosphorylated in a cell cycle-dependent manner that controls its centromere localization during mitotic exit. These results strongly support a model in which the CENP-A assembly machinery is poised for activation throughout the cell cycle but kept in an inactive noncentromeric state by Cdk activity during S, G2, and M phases. Alleviation of this inhibition in G1 phase ensures tight coupling between DNA replication, cell division, and subsequent centromere maturation.